A Comparative Analysis of Local Wisdom in Banjarese and Buginese Folklore: Qualitative Insights for Language Use and Teaching in Education - Irlina, Andi; Djamalie, Zulfa (LET: Linguistics, Literature and English Teaching Journal, 2024)
This study explores the educational values embedded in Banjarese and Buginese folklore through a qualitative descriptive comparison, focusing on the local wisdom and language use present in these cultural narratives. By examining a selection of folk tales from both ethnic groups, the research identifies key themes and moral lessons that reflect the unique socio-cultural contexts of the Banjarese and Buginese communities. Through detailed content analysis, the study reveals how these traditional stories convey ethical teachings, social norms, and cultural heritage, while also illustrating the practical use of language in educational settings. The findings highlight the potential of integrating folklore into modern educational curricula, particularly for language teaching, to foster cultural awareness, moral development, and community values among students. The comparative analysis underscores both the commonalities and unique elements of local wisdom in Banjarese and Buginese folklore, providing educators with valuable insights on utilizing these narratives to enhance language learning and cultural competence. This research contributes to the broader discourse on the role of indigenous knowledge in education, advocating for the preservation and application of folklore to enrich educational content, promote effective language use, and support cultural diversity.